Improving Health Research on Small Populations: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine; Division, Health and Medicine; Services, Board on Health Care; Education, Division of Behavioral and Social Sciences and; Statistics, Committee on National; White, Jordyn; Kirkendall, Nancy (National Academies Press, 2018)
The increasing diversity of population of the United States presents many challenges to conducting health research that is representative and informative. Dispersion and accessibility issues can increase logistical costs; populations for which it is difficult to obtain adequate sample size are also likely to be expensive to study. Hence, even if it is technically feasible to study a small population, it may not be easy to obtain the funding to do so. In order to address the issues associated with improving health research of small populations, the National Academies of Sciences, Engineering, and Medicine convened a workshop in January 2018. Participants considered ways of addressing the challenges of conducting epidemiological studies or intervention research with small population groups, including alternative study designs, innovative methodologies for data collection, and innovative statistical techniques for analysis.